Effect Of Pre-Treatment And Inoculant During Composting Of Palm Oil Empty Fruit Bunches - A. Y. Zahrim; I. K. T. Yee; E. S. C. Thian; S. Y. Heng; J. Janaun; K. P. Chong; S. K. Haywood; V. Tan; T. Asis; T. M. T. M Al Mizi (ASEAN Journal of Chemical Engineering, 2023)
In this work, untreated empty fruit bunch (EFB) or microwave-assisted NaOH pretreated EFB with palm oil mill effluent (POME) were composted under mesophilic conditions either in the presence or absence of Bacillus amyloliquefaciens D203 for sixty days. During pretreatment conditions, the EFB was mixed with 1% (w/w) sodium hydroxide and then exposed to microwave irradiation. The composting process was evaluated based on the evolution of pH, electrical conductivity, moisture content, organic matter loss, zeta potential and phytotoxicity. The strain Bacillus amyloliquefaciens D203 is not suitable for EFB-POME composting due to lower organic matter loss. The microwave-assisted NaOH pretreatment contributed to ~15% more organic matter loss than was found in the untreated sample while its germination index was >50%.